Implementation of online psychosocial interventions for people with neurological conditions and their caregivers: A systematic review protocol. (September 2021) - Miao, Melissa; Power, Emma; Rietdijk, Rachael; Brunner, Melissa; Togher, Leanne
Background: As the burden of neurological conditions increases globally, online psychosocial interventions offer a potentially scalable solution to enabling healthcare access. However, their successful development and implementation require research into electronic healthcare implementation specifically. Methods: Using a search strategy combining the concepts of implementation, electronic healthcare, psychosocial interventions and neurological conditions, we will conduct comprehensive electronic searches for primary implementation evidence in MEDLINE, EMBASE, PsycINFO, CINAHL, Scopus, SpeechBITE and NeuroBITE databases. Included studies will be analysed according to the Non-adoption, Abandonment, Scale-Up, Spread, and Sustainability framework, appraised using the Mixed-Methods Appraisal Tool and evaluated for theoretical underpinning in implementation science, with hybrid studies of effectiveness-implementation research classified according to the type of hybrid design. Discussion: This review will be the first to use a theoretical underpinning in the Non-adoption, Abandonment, Scale-Up, Spread, and Sustainability framework to evaluate strengths and gaps in existing implementation research into online psychosocial interventions for people with neurological conditions and/or their caregivers. The results may be useful to provide direction and recommendations for future clinical implementation and research into online psychosocial interventions for people with neurological conditions and/or their caregivers. Systematic review registration: PROSPERO 2020: CRD42020186387.